2002
DOI: 10.1645/0022-3395(2002)088[0159:eootoe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone Treatment on Eimeria Colchici Oocysts

Abstract: The effect of ozone on the inhibition of the sporulation of Eimeria colchici oocysts in vitro was examined. Lower sporulation ratios were found to correspond directly to longer ozone exposure time. In pheasants, Phasianus colchicus, orally inoculated with ozone-treated oocysts, lower mortality and lower oocysts per gram of feces were observed as compared with birds given untreated oocysts. Thus, treatment of E. colchici oocysts with ozone alone was observed to partially inhibit the growth and infectivity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Thus, new low-cost and eco-friendly anti- Eimeria strategies are urgently required. Alternative therapeutic approaches based on ozone in ruminants ( 51 ) could be useful to control Eimeria infections as demonstrated in poultry ( 56 ). Moreover, recent studies have highlighted the complex network of interactions occurring between protozoa and the gut commensal flora, showing the potential contribution of the intestinal microbiome in the control of parasitic infections ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, new low-cost and eco-friendly anti- Eimeria strategies are urgently required. Alternative therapeutic approaches based on ozone in ruminants ( 51 ) could be useful to control Eimeria infections as demonstrated in poultry ( 56 ). Moreover, recent studies have highlighted the complex network of interactions occurring between protozoa and the gut commensal flora, showing the potential contribution of the intestinal microbiome in the control of parasitic infections ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The treated solution showed near-saturation with ozone after one minute of treatment. However, the ozone treatment in subsequent tests was set at an average temperature of 25 °C with pH = 7 [ 34 , 35 , 36 ]. In order to evaluate the sanitation kinetics, the concentration–time concept was applied, i.e., ozone concentration (C) in mg/L was multiplied by contact-time ( t ) in minutes (C t ) [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…One group was exposed to non-treated water (negative control), as shown in Table 1 . The aliquots of all the groups were centrifuged for 3 min at 170 g and the pellet was resuspended in an aqueous solution of potassium dichromate 2.5% and incubated in a wide-surfaced container at 26–28 °C for 60–72 h, oxygenating the samples several times a day to preserve the oocysts [ 36 ]. At the end of the incubation, each aliquot was centrifuged for three minutes at 170 g, the supernatant was discharged to remove potassium dichromate from the oocyst suspension by repeated dilution with distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is rapidly becoming a precious commodity and wastewater from cities, animal breeding (particularly cattle, sheep, and swine) and industrial plants must be reused for irrigation in order to increase agricultural production. This happens most frequently in underdeveloped countries, but also in the USA and Italy, and poses a health risk by causing serious gastro-intestinal diseases (Stein and Schwartzbrod, 1990 ; Ayres et al, 1992 ; Johnson et al, 1998 ; Orta de Velasquez et al, 2001 ; Liou et al, 2002 ). Toze ( 1999 ) has reported that, in countries with poor sanitation systems, about 250 million people are infected each year by waterborne pathogens, with about 10 million deaths .…”
mentioning
confidence: 99%